A review of Western Palaearctic Amblyscelio and Baryconus (Hymenoptera: Platygastroidea, Platygastridae) - Popovici, Ovidiu Alin; Masner, Lubomir; Notton, David G.; Popovici, Mariana (Zootaxa, 2013)
The European species of the genera Amblyscelio and Baryconus are reviewed and revised based on morphological data. Females of Amblyscelio striaticeps Kieffer, 1913 and Baryconus graeffei (Kieffer, 1908) are described and the ovipositor of Amblyscelio is illustrated for the first time. The monotypic genus Amblyscelio was previously known only from a single male specimen. Baryconus graeffei is confirmed as a distinct species, while B. orbus Kononova, 2008 is recognized as a junior subjective synonym of B. europaeus (Kieffer, 1908) syn. nov. These findings are supported by a principal component analysis (PCA) of ratios of various distance measurements. Amblyscelio striaticeps is newly recorded from Greece and Slovenia, Baryconus graeffei from France, Greece, Montenegro and Turkey and B. europaeus (Kieffer, 1908) from Croatia, France, Morocco, Portugal, Sicily, Spain and the United Arab Emirates.